Nursing diagnosis and Roy´s theoretical model in prostatectomized patients - Elisandra de Araújo Saldanha; Cecília Maria Farias de Queiroz Frazão; Maria Isabel da Conceição Dias Fernandes; Ana Beatriz de Almeida Medeiros; Marcos Venícios de Oliveira Lopes; Ana Luisa Brandão de Carvalho Lira (Universidade Federal do Ceará, 2013)
A descriptive study aimed at identifying the profile of NANDA International nursing diagnoses in patients in the immediate post-operative prostatectomy and relates them to adaptive problems of the Roy Adaptation Model. Conducted in a university hospital in the Northeast of Brazil, between November, 2010 and April, 2011, with a sample of 50 subjects. The collected data were through interviews and physical examinations, with subsequent analysis by means of clinical reasoning. These relations were found: risk of falls and potential injury; impaired ambulation and mobility to walk and/or restricted coordination; self-care deficits and loss of ability to self-care; acute pain and acute pain; insomnia/impaired sleep patterns and sleep deprivation; constipation and constipation. Therefore, most of the nursing diagnoses identified are similar to adaptive problems according to Roy.